Aspek Pendidikan Akhlak Kepada Allah SWT pada Film Hafalan Shalat Delisa - Ifzi Aulia; Indah Muliati (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2022)
The purpose of this study is to analyze aspects of moral education to Allah SWT contained in the film Memorizing Prayers Delisa. The research method used is a qualitative method with a content analysis approach. The data in this study were sourced from the film Memorizing Delisa Prayer which was then supported by supporting data such as from the internet, journals, films, and other references. Researchers act as research instruments. Data collection techniques used are in the form of observation and documentary. While the data analysis that the researcher uses is content analysis technique which includes data collection, data reduction, data presentation, and data verification. The results of this study indicate that this film contains a lot of meaning in each scene, so that film observers can take various values contained in this film. As for the aspect of moral education to Allah SWT in the film Memorizing Delisa Prayers includes three things, namely tawakal to Allah SWT, serving Allah SWT as a form of carrying out Allah's commands and staying away from Allah's prohibitions, and praying to Allah SWT in begging and asking for protection and forgiveness from Allah SWT.